Ozone in Preeclampsia of pregnancy. Case report. (Ozone Therapy Global Journal, 2018)
Preeclampsia is a common pregnancy disorder with important short-term complications for mother and baby. Evidence suggests preeclampsia also has implications for the mother beyond pregnancy, as well as long-term effects on offspring health. The objective of the present study is to determine the effect of ozone therapy administered in form of mayor autohemotherapy in hypertensive pregnant women at her 18th week gestation. Prescribed regular antihypertensive drugs were maintained. The application of ozone significantly (p